Pregnancy outcome in overt hypothyroidism - Singh, Gagan; Kaul, Indu; Singh, Anuradha (International Journal of Research in Medical Sciences, 2016)
Background: To study the pregnancy outcomes in terms of miscarriage, gestational hypertension, preeclampsia, placenta previa, placental abruption, preterm labour, preterm PROM, rate of caesarean section, postpartum hemorrhage, premature birth, low-birth weight, fetal distress in labour, fetal death and congenital anomalies. Methods: The studied subjects included all pregnant women reported to the hospital for a period of one year (November 2012 to October 2013). They were subjected to detailed history, general physical, systemic, local examinations, routine investigations, thyroid function tests (serum TSH, T3, T4) and divided into two groups, Group-I: Overt hypothyroidism (TSH >10Mu/L; T3 and T4 <normal) and Group-II: Euthyroid pregnant women (control group).Outcomes of study group were compared with control group. The data was analyzed using computer software Microsoft Excel and SPSS version 19.0 for Windows. Chi square test was performed to evaluate statistical significance. A p-value of <0.05 was considered as statistically significant. Results: 17045 women reported to hospital during one year period and after applying exclusion criteria 14810 women qualified. Out of these, 14770 pregnant women were found euthyroid and 40 (0.23%) women were overt hypothyroid. Pregnancy outcome like miscarriage (p<0.001), placental abruption (p<0.03), preterm premature rupture of membrane (p=0.003), low birth weight (p<0.001) and premature birth (p=0.003) was found to be statistically significant. Conclusions: Due to adverse pregnancy outcome, women in early pregnancy should be screened for thyroid disorder and those found hypothyroid should be treated.